1-SINF ”ONA TILI VA O‘QISH SAVODXONLIGI” DARSLIGIDAGI ”MENING OILAM” BO‘LIMI USTIDA ISHLASH METODI - Hazratqulov, M. (SCIENCE and SOCIETY, 2022)
Proper organization of primary education means that the process is carried out by the students themselves, not by the teacher, with the participation of the teacher. This article is based on the methods of organizing lessons focusing on conversations.
Keywords: primary education; student; teacher; textbook; lesson; method